Exploratory case study : re-branding China - Lim, Xue Ying (2008)
This Applied Research Report focuses on the issue of poor product quality amidst the manufacturing sector of China which is commonly dubbed ‘the world’s factory’. Through in-depth understanding of the dynamics of the country’s manufacturing sector, consumers’ perception of Chinese-made products, and negative as well as positive aspects of other countries’ manufacturing sectors, this report attempts to conduct an analysis of the “Made-in-China” phenomenon and thereby identify the problems and possible solutions to improve the image of the Chinese label.